Determinants related to the attack tempo in high level male volleyball - Araujo, R.; Moraes, C.; Coutinho, P.; Mesquita, I. (World Congress of Performance Analysis of Sport IX, 2012)
Volleyball game presents a cyclical and sequential pattern which implies that previous actions influence the next ones (Palao et al., 2004). In high level male Volleyball the attack action presents a positive correlation with the game victory (Marcelino et al., 2008). Additionally, attack tempo is a strong indicator of the offensive organization since influence the opponent`s block organization. This study intents to analyse possible determinants that could influence attack tempo in high level male Volleyball. The sample of this study was withdrawn of 1486 serve-reception actions, 1368 set actions and 1344 attack actions, corresponding to 19 games of the 10 best ranked teams of the 2006 FIVB Men`s World Championships. Attack tempo (Castro & Mesquita, 2010) was the dependent variable of this study. In addition, 3 independent variables were considered: serve-reception efficacy; setting zone (Afonso et al. 2012); type of set (Papadimitriou, et al. 2004). A multinomial logistic regression was applied with a significant level established in 5%. Results showed a significant relationship between attack tempo and all considered variables (.2(18) = 694.484, p<0.001). Serve-reception influenced significantly the attack tempo. Excellent serve-reception action (allow all attack options) promoted faster attacks. On the other hand, serve-receptions that not allow a good attack organization promoted slower attacks. Setting zone determines the attack tempo as setting actions performed through reasonable and poor zone induced slower attacks. On the contrary, suspension setting promoted quicker attacks. Although game evolution denote quicker attacks even when conditions are not excellent, serve-reception and setting action showed to have influence on the velocity of the offensive organization. In this way, these results showed that quicker attacks resulted from offensive constraints, more specifically from serve-reception, setting zone and type of set. These results can have implications for practice, namely the necessity of improve some variables that could promote faster attackers, for instance reception efficacy.